F.A. Mouton, Iron in the Soul: The Leaders of the Official Parliamentary Opposition in South Africa, 1910–1993 (Historia, 2021)
The socio-economic roles played by people in various leadership positions in our past society have implications on the citizenry today and thus warrant a serious inquiry, particularly from a historical perspective. Focusing on this standpoint, F.A. Moutonhas previously published biographical literature on fundamental role players in works such as Voices in the Desert: Margaret and William Ballinger, a Biography (1997); Voorloper: Die Lewe van Schalk Pienaar (2002), and Prophet without Honour, F.S. Malan: Afrikaner, South African and Cape Liberal (2011).
Keywords: Mouton; Afrikaner; apartheid; Dr A.P. Treunicht